REQUALIFICATION AND RISK BASED UNDERWATER INSPECTION (RBUI) PLANNING FOR AN OFFSHORE PLATFORM IN JAVA SEA - Gede Pradnyanata, Dewa
Most of offshore platforms in Indonesia have service life more than 20 years hence required a requalification program for the existing structure to maintain its structural integrity. In requalification program, inspection data is necessary to assess the critical structural component. There is a problem where the cost of underwater inspection is expensive that the annual underwater inspection could not be done. To prevent the problem, a method to determine underwater inspection time interval based on risk level is needed so that the inspection time interval can be enlarged yet the structural integrity can be maintained. In this final project, a 4 legs wellhead platform owned by PT. Pertamina Hulu Energi Offshore North West Java is modelled. The platform was installed in 1985 and still operating to lift oil these days. This platform is located in java sea, northern side of seribu islands with 101.33 ft (MSL) of water depth. The analysis that used for the requalification are design level analysis and ultimate strength analysis. The design level analysis consists of 3 analysis, that are inplace, seismic, and fatigue analysis. These analyses carried out the examination of member unity check, joint punching shear, pile axial capacity, deflection, and joint/member fatigue life. Pushover is performed in the ultimate strength analysis with wave loading. This analysis carried out the examination of structural reserve strength ratio (RSR) and plasticity of critical member resulted from design level analysis. Based on the requalification result, installment of stiffener is needed at critical member of 1247-1243 (UC=1.88 to 0.78), 1281-1273 (UC=1.15 to 0.65), and 1319-1317 (UC=1.39 to 0.56). The stiffener to be installed are 3 parts of W10x100 stiffener and 8 parts of C6x8 stiffener at cellar deck. From the seismic analysis, there are decks with exceeding deflection yet could be tolerated for an 800-years earthquake with a small difference between the actual deflection and the allowable deflection, it is 0.09 inch. From the fatigue analysis, there are 4 joints with remaining fatigue life is exceeded compare to the structure service life (35 years). The 4 joints are joint 366 (17.75 years), joint 356 (17.99 years), joint 341 (18.51 years), and joint 371 (23.15 years). These joints are required for complete and detailed inspection on the next inspection program. From the ultimate strength analysis result, the minimum RSR of the structure is 1.92 with the wave loading direction is 90 degrees of the platform. From the RBUI analysis, the platform is categorized as L-2 based on the exposure level and the inspection interval based on the risk level is every 8 years for a major inspection and every 14 years for complete inspection.